Soil fauna in areas with different management and disposal times of animal waste Fauna Edáfica Em Áreas Com Diferentes Manejos E Tempos De Descarte De Resíduos Animais - De Oliveira Filho L.C.I.* (2018)
© 2018 Universidade Federal do Parana 1. All rights reserved.The goal of this study was to evaluate the presence of soil fauna under different managements and times disposal of animal waste. The areas used for the study were differentiated by the following managements: native forest, native pasture without disposal and areas of agricultural use: ryegrass pasture with 5 and 17 years of disposal of animal waste, corn for silage with 9 and 22 years of disposal pasture without grazing with 22 years of disposal. Each season were sampled 9 points per area, with spacing of 30 meters between each point. Were performed fauna assessments (method Berllese and TSBF) and physical and chemical attributes. We used the principal response curve (PRC) to observe the behavior of the areas over time and redundancy analysis (RDA) for the attributes that explain the variability of the soil fauna groups. The pasture area with 22 years was more stable compared the others (except the native forest) how the behavior of the density of organisms over time by CRP. The OM and Cu attributes were significant explanatory variables in ADR for the two techniques considering all the collecting seasons. Continued disposal of animal waste in the soil causes changes in the environment influencing the populations of soil fauna.